Looking beyond the Surface: The Band Gap of Bulk Methylammonium Lead Iodide - Schuster, Oskar; Wientjes, Peter; Shrestha, Shreetu; Levchuk, Ievgen; Sytnyk, Mykhailo; Matt, Gebhard; Osvet, Andres; Batentschuk, Miroslaw; Heiß, Wolfgang; Brabec, Christoph; Fauster, Thomas; Niesner, Daniel (Nano Letters, 2020)
Despite the intense research on photovoltaic lead halide perovskites, reported optical properties as basic as the absorption onset and the optical band gap vary significantly. To unambiguously answer the question whether the discrepancies are a result of differences between bulk and "near-surface" material, we perform two nonlinear spectroscopies with drastically different information depths on single crystals of the prototypical (CH3NH3)PbI3 methylammonium lead iodide. Two-photon absorption, detected via the resulting generation of carriers and photocurrents (2PI-PC), probes the interband transitions with an information depth in the millimeter range relevant for bulk (single-crystal) material. In contrast, the transient magneto-optical Kerr effect (trMOKE) measured in a reflection geometry determines the excitonic transition energies in the region near (hundreds of nm) the surface which also determine the optical properties in typical thin films. To identify differences between structural phases, we sweep the sample temperature across the orthorhombic-tetragonal phase transition temperature. In the application-relevant room-temperature tetragonal phase (at 170 K), we find a bulk band gap of 1.55 ± 0.01 eV, whereas in the near-surface region excitonic transitions occur at 1.59 ± 0.01 eV. The latter value is consistent with previous reflectance measurements by other groups and considerably higher than the bulk band gap. The small band gap of the bulk material explains the extended infrared absorption of crystalline perovskite solar cells, the low-energy bands which carry optically driven spin-polarized currents, and the narrow bandwidth of crystalline perovskite photodetectors making use of the spectral filtering at the surface.
CRIS-Team Scopus Importer:2020-05-22
Keywords: band gap; CH3NH3PbI3; lead halide perovskite; magneto-optical Kerr effect; nonlinear absorption

Temperature-dependent optical spectra of single-crystal (CH3NH3)PbBr3 cleaved in ultrahigh vacuum - Niesner, Daniel; Schuster, Oskar; Wilhelm, Max; Levchuk, Ievgen; Osvet, Andres; Shrestha, Shreetu; Batentschuk, Miroslaw; Brabec, Christoph; Fauster, Thomas (Physical Review B - Condensed Matter and Materials Physics, 2017)
We measure temperature-dependent one-photon and two-photon induced photoluminescence from (CH3NH3)PbBr3 single crystals cleaved in ultrahigh vacuum. An approach is presented to extract absorption spectra from a comparison of both measurements. Cleaved crystals exhibit broad photoluminescence spectra. We identify the direct optical band gap of 2.31 eV. Below 200 K, the band gap increases with temperature, and it decreases at elevated temperature, as described by the Bose-Einstein model. An excitonic transition is found 22 meV below the band gap at temperatures <200 K. Defect emission occurs at photon energies <2.16 eV. In addition, we observe a transition at 2.25 eV (2.22 eV) in the orthorhombic (tetragonal and cubic) phase. Below 200 K, the associated exciton binding energy is also 22 meV, and the transition redshifts at higher temperature. The binding energy of the exciton related to the direct band gap, in contrast, decreases in the cubic phase. High-energy emission from free carriers is observed with higher intensity than reported in earlier studies. It disappears after exposing the crystals to ai